Association between maternal antibiotic exposure during pregnancy and childhood obesity in the Japan Environment and Children's Study. Issue 11 (24th June 2022) - Sakurai, Kenichi; Yamamoto, Midori; Eguchi, Akifumi; Takatani, Rieko; Watanabe, Masahiro; Mori, Chisato
Summary: Background: The association between maternal antibiotic exposure during pregnancy and childhood obesity is still unclear. Objectives: The study aimed to evaluate the association between prenatal exposure to antibiotics and obesity at age 3 years using data from a large Japanese birth cohort. Methods: The Japan Environment and Children's Study is a nationwide birth cohort study. In this study, singleton vaginal full‐term births were included. Obesity was defined as body mass index ≥95th percentile according to child growth standards. Prenatal antibiotic exposure was defined as antimicrobial agent use during pregnancy and was collected from maternal interviews and medical record transcripts. Logistic regression analysis was performed to evaluate the association of prenatal antibiotic exposure with child obesity at 3 years. Results: In the crude and adjusted models with all children, maternal antibiotic exposure during pregnancy showed a marginal relationship with child obesity at 3 years. In the analyses according to exposure period and sex, exposure to antibiotics during the second/third trimester was significantly associated with obesity at the age of 3 years in female infants, but not in male infants, although the exposure during the first trimester was not in both sexes. Conclusion: Maternal antibiotic exposure during mid/late pregnancy may result in child obesity.